Lowrider Space : Aesthetics and Politics of Mexican American Custom Cars - Chappell, Ben, 1971- (Book collections on Project MUSE., 2012)
"This book explores how lowrider car culture allows Mexican Americans to alter the urban landscape and make a place for themselves in an often segregated society"--